2013
DOI: 10.1111/tmi.12155
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic determinants of HIV testing and counselling: a comparative study in four African countries

Abstract: Objectives Research indicates that individuals tested for HIV have higher socioeconomic status than those not tested, but less is known about how socioeconomic status is associated with modes of testing. We compared individuals tested through provider-initiated testing and counselling (PITC), those tested through voluntary counselling and testing (VCT), and those never tested. Methods Cross-sectional surveys were conducted at health facilities in Burkina Faso, Kenya, Malawi, and Uganda, as part of the MATCH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 25 publications
(40 reference statements)
9
49
0
Order By: Relevance
“…As previously documented, we observed among both men and women that testing uptake increased with educational level and wealth [13, 25, 35, 36]. Similarly, high HIV-related knowledge and access to broader information channels, through media exposure, was associated with HIV testing [3539]. These results highlight the importance of providing health education to both women and men while deploying targeted efforts to reach populations with low uptake of HIV testing.…”
Section: Discussionsupporting
confidence: 80%
“…As previously documented, we observed among both men and women that testing uptake increased with educational level and wealth [13, 25, 35, 36]. Similarly, high HIV-related knowledge and access to broader information channels, through media exposure, was associated with HIV testing [3539]. These results highlight the importance of providing health education to both women and men while deploying targeted efforts to reach populations with low uptake of HIV testing.…”
Section: Discussionsupporting
confidence: 80%
“…20,48,50 In regards to HIV knowledge and awareness, the highest estimates for HIV testing coverage are observed among individuals with medium to higher HIV/AIDS awareness, echoing the results found in the previous studies. 7,13 At community level, community poverty, HIV-related stigma and media exposure were found to be associated with HIV testing. Community level risky sexual behaviour and HIV awareness were not associated with HIV testing, consistent with findings from previous studies.…”
Section: Key Findingsmentioning
confidence: 99%
“…Individuals who are divorced, widowed and married tend to have higher odds of HIV testing than never married individuals. [12][13][14] For example, married individuals were found to be 2.54 times more likely to be tested for HIV than never married individuals in South Africa. 15 Similarly, a study in Ivory Coast 16 found that never married individuals were 66% less likely to be tested than married people.…”
Section: Introductionmentioning
confidence: 99%
“…While a history of childhood sexual violence is not associated with HIV Testing and Counseling (HTC) knowledge or uptake, family wealth was strongly associated. Previous research indicates that HTC knowledge and testing rates are associated with wealth and socioeconomic status in a variety of contexts (Helleringer, Kohler, Frimpong, & Mkandawire, 2009) and has been confirmed in several national surveys in Africa (Central Statistical Office, Ministry of Health, Tropical Diseases Research Center and University of Zambia, & Macro International Inc., 2009; National Statistical Office & ICF Macro, 2011; Obermeyer et al, 2013; Uganda Ministry of Health, 2011). For example, the 2011/2012 Tanzania AIDS Indicator Survey (Tanzania Commission for AIDS Commission, National Bureau of Statistics, Office of the Chief Government Statistician, & ICF International, 2013) found that 83.8% of females in the lowest wealth quintile knew where to go for HIV testing compared to 93.0% in the highest wealth quintile, and 53.4% of females in the lowest quintile had ever been tested for HIV compared to 69.6% in the highest quintile.…”
Section: Discussionmentioning
confidence: 85%